Study of rapid detection of Mycobacterium Tuberculosis through GeneXpert MTB/RIF assay from acid fast bacilli smear-negative specimens in a Tertiary Care Hospital, Biratnagar Nepal - Ragani Yadav, Kumari; Shrestha, kewal (Birat Journal of Health Sciences, 2024)
Introduction: Tuberculosis (TB) is an important public health concern around the world. It is well known that acid-fast bacilli (AFB) smear-negative TB cases are a major source of spreading TB to others when left untreated. Objectives: Our study aim to detect Mycobacterium tuberculosis (MTB) in AFB smear-negative samples through GeneXpert MTB/RIF assay and also to evaluate the drug resistance patterns towards Mycobacterium tuberculosis in hospitals. Methodology: This descriptive cross-sectional study was conducted among smear-negative presumptive TB patients at a tertiary care center with eﬀect from September 2022 to September 2023 after approval from the Institutional Review Committee of the college. A convenience sampling method was used. Results: Out of 653 smear-negative samples, 71 (10.9%) were positive for TB and 17 (2.6%) were rifampicin resistance cases detected by GeneXpert MTB/RIF assay. The cases of tuberculosis were more in age groups between 46->60 years and least in 17-30 years of age. Pulmonary samples yielded a higher number of MTB 66 (92.95%) as compared to extra-pulmonary samples 5 (7.04%). There is an almost equal proportion of mycobacterium infection in males 37(52.11%) and females 34(47.88%). All the rifampicin resistance cases detected in our study were from pulmonary samples. Conclusion: Our study shows that the sensitivity of GeneXpert MTB/RIF assay is higher than AFB smear microscopy. We are missing actual TB cases while using AFB smear microscopy only. Hence the GeneXpert MTB/RIF assay is important for the rapid detection of MTB in smear-negative as well as smear-positive drug resistance MTB cases.